Maternal obesity does not influence human milk protein 15N natural isotope abundance. Issue 4 (4th July 2019) - De Luca, Arnaud; Bernardo, Karine; Frasquet-Darrieux, Marine; Christin, Patricia; Schiphorst, Anne-Marie; Grand, Mathilde; Ingrand, Pierre; Robins, Richard J.; Hankard, Regis
ABSTRACT: Obesity increases protein metabolism with a potential effect on nitrogen isotope fractionation. The aim of this study was to test the influence of obesity on human milk extracted protein 15 N natural isotope abundance (NIA) at one month post-partum and to compare human milk extracted protein 15 N NIA and bulk infant hair 15 N NIA. This cross-sectional observational study involved 16 obese mothers (body mass index (BMI) ≥ 30 kg m −2 before pregnancy) matched with 16 normal-weight mothers (18.5 kg m −2  ≤ BMI < 25 kg m −2 ) for age and pregnancy characteristics. Human milk extracted protein and bulk infant hair 15 N NIA were determined by isotope ratio monitoring by mass spectrometry interfaced to an elemental analyser (IRM-EA/MS). No significant difference was found in human milk protein 15 N NIA values between obese and normal-weight mothers (8.93 ± 0.48 ‰ vs. 8.95 ± 0.27 ‰). However, human milk protein 15 N NIA was significantly lower than bulk infant hair 15 N NIA: 8.94 ± 0.38 ‰ vs. 9.66 ± 0.69 ‰, respectively. On the basis of these results, it is concluded that human milk protein 15 N NIA measured at one month post-partum is not influenced by maternal obesity. These findings suggest that 15 N NIA may be exploited to study metabolism without considering maternal obesity as a confounder.